A Multiple Antigen Peptide Vaccine Containing CD4+ T Cell Epitopes Enhances Humoral Immunity against Trichinella spiralis Infection in Mice - Yuan Gu; Ximeng Sun; Jingjing Huang; Bin Zhan; Xinping Zhu (Journal of Immunology Research)
Multiepitope peptide vaccine has some advantages over traditional recombinant protein vaccine due to its easy and fast production and possible inclusion of multiple protective epitopes of pathogens. However, it is usually poorly immunogenic and needs to conjugate to a large carrier protein. Peptides conjugated to a central lysine core to form multiple antigen peptides (MAPs) will increase the immunogenicity of peptide vaccine. In this study, we constructed a MAP consisting of CD4+ T cell and B cell epitopes of paramyosin (Pmy) of Trichinella spiralis (Ts-Pmy), which has been proved to be a good vaccine candidate in our previous work. The immunogenicity and induced protective immunity of MAP against Trichinella spiralis (T. spiralis) infection were evaluated in mice. We demonstrated that mice immunized with MAP containing CD4+ T cell and B cell epitopes (MAP-TB) induced significantly higher protection against the challenge of T. spiralis larvae (35.5% muscle larva reduction) compared to the MAP containing B cell epitope alone (MAP-B) with a 12.4% muscle larva reduction. The better protection induced by immunization of MAP-TB was correlated with boosted antibody titers (both IgG1 and IgG2a) and mixed Th1/Th2 cytokine production secreted by the splenocytes of immunized mice. Further flow cytometry analysis of lymphocytes in spleens and draining lymph nodes demonstrated that mice immunized with MAP-TB specifically enhanced the generation of T follicular helper (Tfh) cells and germinal center (GC) B cells, while inhibiting follicular regulatory CD4+ T (Tfr) cells and regulatory T (Treg) cells. Immunofluorescence staining of spleen sections also confirmed that MAP-TB vaccination enhanced the formation of GCs. Our results suggest that CD4+ T cell epitope of Ts-Pmy is crucial in vaccine component for inducing better protection against T. spiralis infection.